2x-3y=-12 x=1-2y y=-14 y=-14
x+2y=1 2(1-2y)-3y=-12 x=1-2*(-14) x=-27
2+4y-3y=-12
y=-12-2
y=-14
3x+5y=2 3x=2-5y x=-1-5y x=-1-5*(-0/5) x=1.5
6x+10y=4 6x+10y=4 6(-1-5y)+10y=4 y=-0.5 y=-0.5
-6-30y+10y=4
-30y+10y=4+6
-20y=10
y=-05
x^2-2x-3>=0
D=4
x= -2+4/2=1
x2=-2-4/2=-3
проверим
(-oo;1] U [3;+oo)
x^2-2x-3-2a=x+3+a
x^2-3x-(3a+6)=0
D=9+4(3a+6)>0
9-12a+24>0
-12a+33>0
a>33/12
более одного корня то есть два
теперь
x^2-2x-3-2a=-x-a+3
x^2-x-a-6=0
D=1+4(a+6)>0
4a+25>0
a>-25/4
x^2-2x-3-2a=x+a+3
x^2 -3x- 3a-6=0
3a=x^2-3x-6
a=x^2/3-x-2
Если построить график то можно увидеть что при а=0
y' = -6sin6x +6cos6x
y'(П/8) = -6sin(6*П/8) +6cos(6*П/8) = -6sin(3*П/4) +6cos(3*П/4)
=![-6*\frac{\sqrt{2}}{2} -6*\frac{\sqrt{2}}{2} = -6\sqrt{2}](/tpl/images/0119/9716/24ccf.png)